V-doped Co-free Li-rich layered oxide with enhanced oxygen redox reversibility for excellent voltage stability and high initial Coulombic efficiency - Liping Tan; Wenzhao Huang; Xiaoyan Xie; Xiaola Li; Ziyang Liang; Zhan Lin; Chenyu Liu; Dong Luo (Energy Materials and Devices)
Li-rich Mn-based oxides (LRMOs) hold great promise as next-generation cathode materials for high-energy Li-ion batteries because of their low cost and high capacity. Nevertheless, the practical application of LRMOs is impeded by their low initial Coulombic efficiency and rapid voltage decay. Herein, a V-doped layered-spinel coherent layer is constructed on the surface of a Co-free LRMO through a simple treatment with NH4VO3. The layered-spinel coherent layer with 3D ion channels enhanced Li+ diffusion efficiency, mitigates surface–interface reactions and suppresses irreversible oxygen release. Notably, V-doping significantly reduces the Bader charge of oxygen atoms, thereby impeding excessive oxidation of oxygen ions and further enhancing the stability of O-redox. The modified LRMO exhibites a remarkable initial Coulombic efficiency of 91.6%, significantly surpassing that of the original LRMO (74.4%). Furthermore, the treated sample showes an impressive capacity retention rate of 91.9% after 200 cycles, accompanied by a voltage decay of merely 0.47 mV per cycle. The proposed treatment approach is straightforward and significantly improves the initial Coulombic efficiency, voltage stability, and capacity stability of LRMO cathode materials, thus holding considerable promise for the development of high-energy Li-ion batteries.